Improvement of Oil/Water Selectivity by Stearic Acid Modified Expanded Perlite for Oil Spill Cleanup - 祁佩时 林娜 刘云芝 赵俊杰 (Shanghai jiao tong da xue xue bao, 2013)
Ecological disasters and economic losses resulting from oil spills have reminded us the necessity for finding an environmentally friendly, cost-effective, and available in large-scale materials to minimize the oil spill effects. The development of high oil/water selectivity mineral sorbent for the removal of oil from the water is of great interest for oil spill cleanup. In this work, highly oil/water selectivity sorbent of expanded perlite modified with stearic acid was prepared by solution-immersion processes, and the characterization of sorbent was analyzed by Fourier transformation infrared （FT-IR） spectroscopy technique. The optimized amount of loaded stearic acid （SA） on the expanded perlite surface was found to be 2.0%. Then the sorption characteristics of unmodified expanded perlite （UMEP） and stearic acid modified expanded perlite （SMEP） were tested. The effects of different particles size, oil/water volume ratio and sorption simulated condition were investigated. It was found that expanded perlite modified with stearic acid could adsorb selectively oil from water in oil/water system. The maximum oil/water sorption ratio of SMEP was 46, which was about 191 times that of UMEP （0.24） in studied experimental range. The FT-IR analysis demonstrated the presence of long-chain alkyl group in the SMEP samples, which played an important role in oil/water selectivity of SMEP samples. The equilibrium were tested with Langmuir and Freundlich isotherm models, and oil sorption process of SMEP showed good correlation with the Langmuir isotherm model.